2004
DOI: 10.1074/jbc.m400357200
|View full text |Cite
|
Sign up to set email alerts
|

The FlgS/FlgR Two-component Signal Transduction System Regulates the fla Regulon in Campylobacter jejuni

Abstract: The human pathogen Campylobacter jejuni is a highly motile organism that carries a flagellum on each pole. The flagellar motility is regarded as an important trait in C. jejuni colonization of the intestinal tract, however, the knowledge of the regulation of this important colonization factor is rudimentary. We demonstrate by phosphorylation assays that the sensor FlgS and the response regulator FlgR form a two-component system that is on the top of the Campylobacter flagellum hierarchy. Phosphorylated FlgR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
193
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(201 citation statements)
references
References 63 publications
6
193
0
2
Order By: Relevance
“…Hendrixson & DiRita (2003) also confirmed the predicted identity of Cj0793 (named flgS) as the gene encoding the cognate sensor for FlgR (Jagannathan et al, 2001), forming a two-component sensor-regulator system controlling s 54 . Wosten et al (2004) have confirmed that a phospho-transfer relay mediates this two-component regulation. Using microarrays and proteomic analyses to investigate variants of strain NCTC 11168, Carrillo et al (2004) have demonstrated the importance of genes with predicted promoters dependent on s 54 and s 28 in motility-associated attenuation of a poorly motile stock strain, identified middle and late genes involved in the flagellar gene expression cascade, and demonstrated key roles for flhA and fliA.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Hendrixson & DiRita (2003) also confirmed the predicted identity of Cj0793 (named flgS) as the gene encoding the cognate sensor for FlgR (Jagannathan et al, 2001), forming a two-component sensor-regulator system controlling s 54 . Wosten et al (2004) have confirmed that a phospho-transfer relay mediates this two-component regulation. Using microarrays and proteomic analyses to investigate variants of strain NCTC 11168, Carrillo et al (2004) have demonstrated the importance of genes with predicted promoters dependent on s 54 and s 28 in motility-associated attenuation of a poorly motile stock strain, identified middle and late genes involved in the flagellar gene expression cascade, and demonstrated key roles for flhA and fliA.…”
Section: Introductionsupporting
confidence: 53%
“…The observation that transcription of fliA, encoding s 28 and other genes in the Cj0062c-fliY gene cluster, appears from the fliK mutant experiment to be s 54 -dependent is novel; these genes were earlier predicted to be transcribed from a s 70 -dependent promoter (Carrillo et al, 2004;Wosten et al, 2004). Transcription is presumably initiated from the apparent s 54 -dependent canonical promoter element located upstream of Cj0062c and within the coding sequence of Cj0063c (flhG) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CbrR modulates the Campylobacter response to bile, but its cognate sensor kinase and the target genes controlled by it are unknown (36). The FlgSR system controls the flagellar regulon and affects the motility of Campylobacter (50). It was also found that FlaR undergoes phase variation due to the presence of homopolymeric tracts of adenine and thymine in the coding gene (13).…”
mentioning
confidence: 97%
“…In C. jejuni NCTC 11168 and RM1221, each system has nine response regulators and six histidine sensor kinases (9,32). Several of the regulators or TCR systems, including DccRS (28), PhosSR (49), FlgSR (50), CbrR (36), RacRS (4), and CheY (53), have been studied, and all were found to be required for Campylobacter colonization in vivo. The RacRS system is responsive to temperature and controls the expression of multiple proteins in C. jejuni, while the PhosSR system senses phosphate conditions and modulates the expression of 12 genes that are involved in phosphate transport and utilization (4,49).…”
mentioning
confidence: 99%